Lower Devonian faunas and palynomorphs from the Dornes Syncline (Central Iberian Zone, Portugal): stratigraphical and paleogeographical implications - Gourvennec Rémy; Piçarra José Manuel; Plusquellec Yves; Pereira Zélia; Oliveira José Tomás; Robardet Michel (Carnets de Géologie, 2010)
In the Dornes syncline, southern Central Iberian Zone, Portugal, the uppermost levels of the Serra do Luação Formation up to now have been considered to be of Pridoli-Lochkovian? age because they lie immediately under the Dornes Formation, which is of Pragian age and is well defined stratigraphically. New paleontological elements including benthic faunas and palynomorphs allow us to confirm that the top of the Serra do Luação Formation is securely Lochkovian, for upper Lochkovian strata are present although relatively thin. The transition from the Serra do Luação to the Dornes formations and their lithostratigraphical relationship are now clear: the terrigenous succession belongs to the Serra do Luação Formation and the limestones represent the Dornes Formation. The benthic faunas clearly have North-Gondwanan affinities.